Unravelling the metabolic and immunological impacts of helicobacter pylori eradication in healthy adult/youth through omics / Theresa Yap Wan Chen - Theresa Yap, Wan Chen (2017)
Helicobacter pylori is an important bacterial aetiological agent of gastroduodenal diseases. H. pylori positivity is also a risk factor for gastric adenocarcinoma and MALT lymphoma. Ironically, accumulating evidence demonstrates that H. pylori may protect the human host against obesity and atopic disorders. We hypothesised that disappearance H. pylori leads to changes in the human gut microbiome resulting in local and systemic changes in metabolism that may contribute to eventual development of undesirable metabolic and immunological disorders. This study was therefore, carried out to investigate the implications of H. pylori eradication and the association with metabolic and immunological disorders in a young healthy adult population. From 573 healthy adult volunteers (18-30 years-old) screened, the prevalence of H. pylori infection was 9.9%. Eventually, 29 H. pylori-positive subjects were enrolled and assessed during baseline followed by 6, 12 and 18 months post-H. pylori eradication. Faecal metagenomics and lipidomics were used to evaluate the local effects following H. pylori eradication on the gut microbiota and further metabolic, immunological and plasma metabolomic studies were performed to reflect the systemic effects of H. pylori eradication. The impact of H. pylori on the human gut microbiome pre- and post eradication was investigated using 16S rRNA gene (V3-V4 region) sequencing and data analysis using Qiime pipeline. The local and systemic effects of H. pylori, post eradication, were examined through untargeted faecal lipidomics and plasma metabolomics using liquid chromatography mass spectrometry (LC-MS). The effect of H. pylori eradication on meal-associated changes on gastrointestinal metabolic hormones, cytokines and Immunolglobulin E (IgE) antibody level were evaluated using a multiplex bead assay and enzyme-linked immunosorbent assay, correspondingly. The microbial diversity was found to be similar pre- and post-H. pylori eradication with no iv significant differences in bacterial richness and evenness. Despite that, some changes in the bacterial communities at the phylum and genus levels were notable, particularly the decrease in relative abundance of Bacterioidetes and the corresponding increase in Firmicutes following H. pylori eradication. The significant increase of short-chain fatty acids (SCFA)-producing bacteria genera could also be associated with increased risk of metabolic disorders. Faecal lipidomics and plasma metabolomics revealed that eradication of H. pylori dramatically changed many global metabolite/lipid features, with the majority of them being down-regulated. The influence of gut microbiota on plasma metabolites profile was also demonstrated. These findings primarily implicate the perturbation of gut microbiota following H. pylori eradication in host energy and lipid metabolism which may eventually lead to the development of metabolic disorders. Metabolic studies demonstrated that H. pylori eradication was associated with long-term disturbance in active amylin, pancreatic polypeptide and total peptide YY both pre- and post-prandially and glucagon-like peptide-1 post-prandially (p<0.05). An inverse association between H. pylori infection and allergen specific-IgE antibodies (p<0.05) was observed. The predictive metabolic signature of metabolic and immunological disorders following H. pylori eradication may give us insights on complex interaction of H. pylori with gut microbiota, the importance of biosis of the gut microbiota and their implications in human health. In conclusion, eradication of H. pylori demonstrated intricate and complex interactions between H. pylori and the gut microbiota in modulating human health and therefore, a point to ponder upon future management of H. pylori infection.